Phase and morphology of calcium carbonate precipitated by rapid mixing in the absence of additives. Issue 30 (4th July 2022) - Song, Kyungsun; Bang, Jun-Hwan; Chae, Soo-Chun; Kim, Jeongyun; Lee, Seung-Woo
Abstract : Vaterite with various polymorphs was prepared using different solution pH values. The effects of local solution differences in pH were systematically investigated. Abstract : Calcium carbonate is one of the most common minerals, and its polymorphic formation and transformation pathways from the amorphous to crystalline phases are well documented. However, the effects of locally created pH changes on the preferential formation of amorphous calcium carbonate (ACC) or its crystalline phase remain poorly understood. In this study, the influence of the initial solution pH on the precipitated polymorphs of calcium carbonate was investigated by the rapid mixing of each solution containing calcium or carbonate ions in the absence of additives. The results showed that the amount of recovered ACC particles was associated with the availability of fully deprotonated carbonate ions. A secondary crystalline phase was identified as the vaterite phase, but no polymorphic change to produce the more stable calcite was detected during 5 h of stirring. Interestingly, during the early stage of pouring, the vaterite morphology was dependent on the generated pH range, over which ACC particles were stabilized (pH > 10.3), followed by the hydration–condensation processes. When the pH was sufficiently low (pH < 10.3) for bicarbonate ions to participate in the carbonation reaction, croissant- or cauliflower-like aggregates with layered structures were obtained. In contrast, typical spherical vaterite particles were obtained at a high initial pH when the carbonate ions were dominant. Meanwhile, vaterite particles that were formed in the presence of an excess of carbonate ions were irregular and separate agglomerates. These results elucidate the formation of ACC and the morphologies of the vaterite products.